URGENSI PENDIDIKAN KARAKTER DALAM MENGHADAPI KENAKALAN REMAJA DI MI NURUL HUDA PANGENAN - ayunuraeni; Jiada Yahya (IAIC (Institut Agama Islam Cirebon), 2021)
The writing of this article explains the urgency of character education in the face of juvenile delinquency. This study was conducted on students of mi nurul huda. This research method uses descriptive methods with trigulation data collection techniques. Based on observations made, the formation of important characters is applied early on to prepare themselves so as not to be affected by association. Character education is not only with material but also requires habituation and monitoring of Teachers and parents.